Influência da densidade básica da madeira de clones de Eucalyptus grandis x Eucalyptus urophylla na qualidade da polpa branqueada. - dos Santos, Sheila Rodrigues; Sansigolo, Claudio Angeli (Universidade Federal de Santa Maria (UFSM), Centro Pesquisas Florestais, 2007)
The study analyzed the wood basic density effect in two Eucalyptus grandis x Eucalyptus urophylla hybrid clones (440 kg/m(3) e 508 kg/m(3)) on bleached pulp quality (fiber dimensions and physical-mechanical properties). The woods performance on pulping, bleaching and beating results were analyzed. The Kraft pulping was carried out in forced circulation digester in order to obtain 17 +/- 1 kappa number targets. The pulps were bleached to 90 +/- 1 using delignification oxygen and D0EOPD1 bleaching sequence. Bleached pulp of low basic density clone showed, significantly, lowest revolutions number in the PFI mill to reach tensile index of 70 N.m/g, low Schopper Riegler degree and generated sheets with higher values to bulk and opacity. These characteristics and properties allow concluding that bleached pulp of low basic density clone was the most indicated to produce printing and writing sheets. The bleached pulp of high basic density clone showed higher values of bulk and capillarity Klemm and lower water retention value when analyzed without beating. The bleached pulp of high basic density clone showed more favorable characteristics to the production of tissue papers.
Wood basic density effect of Eucalyptus grandis x Eucalyptus urophylla clones on bleached pulp quality
Keywords: basic density; Kraft pulping; clones; bleaching pulp properties.